Representation of English front vowels by Malay-English bilinguals - Yap, Ngee Thai; Wong, Bee Eng; Abdul Aziz, Adi Yasran (Universiti Putra Malaysia Press, 2010)
This paper presents the results of a study conducted to investigate the representation of English vowels among Malay-English bilingual speakers. The study focused on five front vowels of English. There is a tense-lax contrast in high- and mid-vowels in English (Davenport and Hannahs, 2005; Fromkin, Rodman and Hyams, 2003), but this contrast does not exist anywhere in Malay (Nik Safiah et al., 2008). Thus, a forced choice identification task is constructed with PRAAT (Boersma and Weenick, 2009). Stimuli for the experiment were synthesized using the AT&T text-to-speech demo programme available from AT&T Labs. The values of the first and second formants of the vowels were checked to make sure that they were within the range given in the literature. Fifty-two Malay-English bilingual undergraduates participated in this study. The results showed that Malay-English bilinguals have only three categories of contrast for the front vowels. These results show that the vowel representation of the second language in Malay-English bilinguals is similar to the representation of vowels in the first language.